Negative association between serum calcium and glucocorticoid-induced hypertension in thyroid-associated ophthalmopathy patients treated with methylprednisolone - Wang, Ling; Sun, Yushi; Zhang, Meng; He, Hairong; Wang, Jingya; Xu, Huayang; Hao, Yang; Zhang, Wenqiang; Wang, Yawen; Chong, Kelvin K. L.; Guo, Hui; Shi, Bingyin; et al. (Frontiers in Endocrinology, 2025)
BackgroundHypertension is a common adverse event after systemic glucocorticoid therapy. Previous studies have suggested that blood pressure (BP) regulation is related to serum calcium. However, whether serum calcium affects the risk of glucocorticoid-induced hypertension remains understudied.MethodsWe used data from thyroid-associated ophthalmopathy (TAO) patients who completed a course of intravenous methylprednisolone (IVMP). Patients with high BP at baseline, a history of hypertension, and missing data were excluded. Glucocorticoid-induced hypertension was defined as systolic BP (SBP) ≥ 140 mmHg or diastolic BP (DBP) ≥ 90 mmHg during follow-up. Multivariate logistic regression and generalized additive models were used to investigate the associations between serum calcium and glucocorticoid-induced hypertension. Bar charts were used to compare the SBP and DBP fluctuations between patients with and without hypocalcemia. After accounting for missing data, all analyses were repeated in the imputed cohort.ResultsSerum calcium was negatively correlated with glucocorticoid-induced hypertension after adjusting for covariates with p-value < 0.1 (including age, body mass index, SBP, and DBP). For each 0.1 mmol/L increase in serum calcium, the OR (95% CI) was 0.61 (0.39, 0.95). Furthermore, a nonlinear relationship was observed, with an inflection point at 2.10 mmol/L. After the serum calcium level was converted into a categorical variable, hypocalcemia was positively associated with glucocorticoid-induced hypertension (OR = 3.26, 95% CI = 1.11–9.53). Patients with hypocalcemia exhibited significantly greater SBP fluctuations than patients without hypocalcemia (p < 0.05). These results were stable when adjusting for confounders and in the analyses of the imputed cohort.ConclusionsHypocalcemia was associated with glucocorticoid-induced hypertension in TAO patients. Further research is needed to confirm these findings in larger populations and to investigate whether calcium supplementation before glucocorticoid therapy may reduce such risk.